Analysis Performance of the Bubbling Fluidized Bed Gasifier - Surender Antil, Gulshan Sachdeva (International Journal of Advanced Science and Technology, 2020)
The bubbling fluidized bed gasifier is the one most important technology of the gasification through which biomass fuel is partially ignited in the presence of air and then converted into high calorific value gases fuel. The performance of gasifier is affected by feedstock characteristics, process parameters and design parameters. The focus of the this paper to analyze the performance of the gasifier in terms of product gas composition, heat value and cold gas efficiency by the influence of operating parameters such as equivalence ratio, temperature and fuel consumption rate. From studies and analysis, it is observed that the equivalence ratio is the very important process parameter through which temperature; product gas composition, heat value, and gasification efficiency are affected. When the equivalence ratio increases, the calorific value of product gas and gasification efficiency is decreased.